A Dose-Limited Dexamethasone and Bubble Continuous Positive Airway Pressure in Ventilation-Dependent Extremely Premature Infants - Mohamed, Mohamed A.; Bergman, Aaron; Abdelatif, Dinan; Massa-Buck, Beri (American Journal of Perinatology, 2022)
Objective Dexamethasone has been associated with early extubation and shorter duration of mechanical ventilation in preterm infants. High doses or prolonged courses of dexamethasone may be associated with poor neurodevelopmental outcomes.Study Design This is an observational cohort study assessing the efficacy of a low-dose short dexamethasone course combined with postextubation bubble continuous positive airway pressure (bCPAP) strategy on rates of successful extubation and reduction of the duration of invasive mechanical ventilation in extremely preterm infants. We compared the short-term outcomes of implementing such strategy on a group of infants with birth weight <750 g to a historical cohort.Results Among infants intubated for at least 10 days, median time to extubation from starting the dexamethasone course was 2 days (interquartile range: 1–3). Total duration of intubation was significantly shorter in infants who received dexamethasone compared with the control groups (21 ± 6 vs. 30 ± 10 days, p = 0.03), and although statistically nonsignificant, duration to wean to 21% bCPAP was shorter compared with the control group (48 ± 13 vs. 74 ± 29 days, p = 0.06).Conclusion A low-dose short dexamethasone course combined with postextubation bCPAP intervention may be associated with successful early extubation and shorter duration of mechanical ventilation.Key Points
Keywords: dexamethasone; extremely premature infants; bubble continuous positive airway pressure; chronic lung disease